Persepsi Petani Terhadap Inovasi Budidaya Kopi Robusta Organik di Kabupaten Lampung Barat - Imani, Septiani Nurul; Sukaryana, Yana; Dulbari, Dulbari (Universitas Galuh, 2024)
West Lampung Regency is one of the coffee-producing centers in Lampung Province. This research was conducted in three sub-districts located in West Lampung Regency, namely Sumber Jaya District, Way Tenong District, and Air Hitam District. This research was conducted in three farmer groups that have cultivated organic robusta coffee, namely the Ampera farmer group, the Langgeng Mulyo farmer group, and the BUMP Gapoktan Lampung Robusta farmer group. The purpose of this study was to examine farmers' perceptions of organic robusta coffee cultivation innovations in West Lampung Regency. The research method was carried out using primary data and secondary data. Data analysis was carried out descriptively quantitatively with the help of tabulation analysis tools. Study results showed that farmers' perceptions of organic robusta coffee cultivation innovations as seen from five characteristic aspects were classified as high or good with a yield value of 76 percent. Keywords: perception, innovation, organic coffee.